La entrevista y el interrogatorio como técnicas en la investigación criminal (2016)
Crime investigation must be based on objective methods, and the forensic sciences use the scientific method in their analysis. The interview and the testimony are fundamental parts in the criminal process, to carry them out they must be developed from some objective criteria. To address this issue we will deal with a case in which two patrolmen were in service in the neighborhood modeling patrolling in their jurisdiction, when they hear the communal alarm that is two blocks away, they move to verify that it happens, a subject realizing the presence Of the patrol fires and the patrolman JAIME GONZALEZ unfastens his weapon and repels the attack but receives a shot in one leg, when he asks the support of his companion to face the delinquent this runs running leaving the place which facilitates the escape of the assailant , When the support patrol arrives they manage the transfer of the injured policeman to the central hospital. From the facts it is important to collect the testimonies of witnesses who could witness the facts, in order to determine the criminal profile of the perpetrator